Congregações religiosas, religiosidade e educação em Vale Vêneto – RS (1886-1945) - Cruz, Jorge Vinicius Quevedo da (2019)
This abstract has the purpose of presenting the dissertation entitled "religious congregations, religiosity and education in Vale Vêneto – RS (1886-1945)". From the bibliographical and documentary research we seek to demonstrate how the present religiosity among the Italian immigrants established in Vale Vêneto, community located in the region of the Fourth Immigration Colony of the State of Rio Grande do Sul, manifested through works built in the colonial nucleus, due to the presence of the Catholic Church which saw in education a way of strengthening the ties of cultural identity of immigrants who were mostly catholics.The settlers sought through the Church a form of progress for that region. On the other hand, the religious institution saw in the emigration of Italians to the South of Brazil a way of reinforcing the power and influence of the romanized clergy. In this context, the Pallottine Congregation and the Sisters of the Immaculate Heart of Mary played an important role among the inhabitants of that region through the construction of a network of religious and educational assistance. Therefore, we question the role of these religious congregations in the construction of forms of sociability, at the same time, creating bases for the organization of a religious field favorable to catholicism. This study aims to understand how religiousness among a group of Italian immigrants played an important role in the process of formation of the locality of Vale Vêneto, through the effort of its inhabitants who sought to build a link between religious, education and community life. This work is linked to the activities developed in the Research Line "Culture, Migrations and Labor", of the Graduate-Program in History of the Federal University of Santa Maria.